Legal Protection For The Medical Profession In Treating Unconscious Emergency Patients Without Informed Consent - Indah Mira Tiaraputri Wijaya; Erikson Sihotang; Ni Ketut Wiratny (International Journal Labs, 2024)
The legal relationship between doctors and patients is a relationship based on trust. Legal protection for the medical profession in treating emergency patients without medical approval (informed consent) is regulated in Article 1338 of the Civil Code. The agreement remains binding on both parties, even though the conditions in Article 1320 of the Civil Code are not fulfilled, there are laws that specifically regulate informed consent and Article 1354 of the Civil Code, so that the therapeutic agreement or therapeutic transaction still exists and occurs. As a result, doctors are obliged to provide an achievement to the patient, namely making an effort by providing health services as an effort to cure the patient. In carrying out this effort, doctors must do it with all seriousness by using all the abilities and skills they have while being guided by standards.